Analisis Kinerja Keuangan Terhadap Harga Saham Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia - Rahmah Apriliani; Diah Yudhawati; Muhammad Nur Rizqi (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to find out whether the Profitability Ratio, Liquidity Ratio and Solvency Ratio have an effect either simultaneously or simultaneously on Telecommunication Companies listed on the Indonesia Stock Exchange (BEI). The variables used in this research are Return On Asset Current Ratio and Debt to Equity Ratio. The population used in this research was 22 companies and the sample that met the criteria (purportive sampling) was 8 companies. Data collection techniques in this research use documentation techniques and literature studies used in this research are secondary data sources published by the official website of the Indonesia Stock Exchange (BEI) www.idx.co.id. The data analysis techniques in this research are descriptive analysis techniques, panel data regression, multiple linear analysis techniques, hypothesis testing and coefficient of determination. Data processing uses EVIEWS version 12. The research results partially have profitability and solvency having a significant effect on stock prices but partially liquidity has no significant effect on stock prices. Simultaneously, profitability, liquidity and solvency have a significant effect on the share prices of telecommunications companies listed on the Indonesia Stock Exchange (BEI).